Grb2 carboxyl-terminal SH3 domain can bivalently associate with two ligands, in an SH3 dependent manner - Richa Arya (Nature Portfolio, 2017)
Abstract Src homology domain containing leukocyte protein of 65 kDa (SLP65), the growth factor receptor binding protein 2 (Grb2), and the guanine nucleotide exchange factor for the Rho family GTPases (Vav), self associate in unstimulated B cells as components of the preformed B cell receptor transducer module, in an SH3-dependent manner. The complex enables the B cell to promptly respond to BCR aggregation, resulting in signal amplification. It also facilitates Vav translocation to the membrane rafts, for activation. Here we uncover the molecular mechanism by which the complex may be formed in the B cell. The C-terminal SH3 domain (SH3C) of Grb2 bivalently interacts with the atypical non-PxxP proline rich region of SLP65, and the N-terminal SH3 domain (SH3N) of Vav, both the interactions crucial for the proper functioning of the B cell. Most surprisingly, the two ligands bind the same ligand binding site on the surface of Grb2 SH3C. Addition of SLP65 peptide to the Grb2-Vav complex abrogates the interaction completely, displacing Vav. However, the addition of Vav SH3N to the SLP65-Grb2 binary complex, results in a trimeric complex. Extrapolating these results to the in vivo conditions, Grb2 should bind the SLP65 transducer module first, and then Vav should associate.